إعداد المادة التعليمية لمهارة الكلام من الحوار القرآني في سورة الكهف نموذجا - Hamim, Hamim (UIN Maulana Malik Ibrahim Malang, 2021)
The background of the research comes from learners’ difficulties in developing their language competencies especially speaking skill. Therefore, Arabic learning for foreign learner needs a good quality of speaking skill. It is really necessary to develop their speaking skill through good expressions and grammar in speaking especially for advanced learner.In this case, the researcher found that learners of Arabic speaking skill are still poor and uncreative because learners still do not notice the art of Arabic speaking. Through this underlying reason, the researcher composes sample of Arabic learning material for speaking skill inspired from dialogue within Al Quran in Surah Al Kahfi. Hence, it leads to the question about the appropriate example in Surah Al Kahfi which is suitable for learning Arabic speaking skill.This research uses descriptive analysis method consisting of: 1) Data Resource, 2) Data Collection, 3) Data Analysis, 4) Composing Learning Material.The result of this research shows that: 1) the dialogue within Al Quran in Surah Al Kahfi consists of three kinds of dialogue with various forms and models; 2) the dialogue within Al Quran in Surah Al Kahfi has special features which are able to be inspiration as learning model to sharpen Arabic speaking skill; 3) the dialogue within Al Quran in Surah Al Kahfi can be a guidance in composing learning material especially for speaking with artistic Arabic expressions.